The role of perceived value and green consumption attitude on purchase intention of eco-bag : a study on young consumers - Hassan, H.M. Kamrul; Quader, Mohammed Shahedul; Aktar, Salma (Penerbit Universiti Kebangsaan Malaysia, 2022)
In recent decades, consumers have been eventually shifting towards responsive green consumption behaviour. This study will examine the role of the perceived value (social value, environmental value and economic value) on green consumption attitude and which, in turn, affects young consumers' purchase intention towards eco-bag. A conceptual model was adopted by developing hypotheses and analysed through structural equation modelling. The survey was performed where data were obtained from 373 young consumers from Chattogram, the commercial capital of Bangladesh. The empirical results suggest that economic value, social value and environmental value have a significant and positive influence on the green consumption attitude. Furthermore, green consumption attitude is also found to be a critical factor influencing the intention of young consumers for purchasing eco-bag. This research will help marketers, policymakers, and concerned stakeholders to create awareness among customers regarding eco-bag usage benefits and drive the industry towards sustainability and enhance green revolution to the competitive market structure.